Analysis of Business Process Reengineering in Administrative Service in Ngebel Sub District Office of Ponorogo Regency of East Java Province, Indonesia (International Journal of Scientific Research and Management (IJSRM), 2022)
This research aims to analyze problem and to design procedure in administrative service in Ngebel Sub District Office of Ponorogo Regency. This research was conducted through interview, observation, and documentation. Informant as the data source of research is internal informant (service provider) and external informant (service user). The method used in deciding the data source was purposive sampling method. The result of research showed that based on the result of fishbone/cause-effect and value added analyses on administrative service held, some classical problems were still found. The administrative service procedure analyzed had Value Added Ratio of 86.36% and thereby needed improvement. The problems existing need business process reengineering on administrative service in order to support the achievement of objective, an effective and efficient administrative service. The analysis of the business process reengineering result using Business Impact Analysis showed 21 positive and 8 negative values, and thereby this result is feasible to be implemented further.